Gut liver brain axis in diseases: the implications for therapeutic interventions - Mengyao Yan; Shuli Man; Benyue Sun; Long Ma; Lanping Guo; Luqi Huang; Wenyuan Gao (Signal Transduction and Targeted Therapy, 2023)
Abstract Gut-liver-brain axis is a three-way highway of information interaction system among the gastrointestinal tract, liver, and nervous systems. In the past few decades, breakthrough progress has been made in the gut liver brain axis, mainly through understanding its formation mechanism and increasing treatment strategies. In this review, we discuss various complex networks including barrier permeability, gut hormones, gut microbial metabolites, vagus nerve, neurotransmitters, immunity, brain toxic metabolites, β-amyloid (Aβ) metabolism, and epigenetic regulation in the gut-liver-brain axis. Some therapies containing antibiotics, probiotics, prebiotics, synbiotics, fecal microbiota transplantation (FMT), polyphenols, low FODMAP diet and nanotechnology application regulate the gut liver brain axis. Besides, some special treatments targeting gut-liver axis include farnesoid X receptor (FXR) agonists, takeda G protein-coupled receptor 5 (TGR5) agonists, glucagon-like peptide-1 (GLP-1) receptor antagonists and fibroblast growth factor 19 (FGF19) analogs. Targeting gut-brain axis embraces cognitive behavioral therapy (CBT), antidepressants and tryptophan metabolism-related therapies. Targeting liver-brain axis contains epigenetic regulation and Aβ metabolism-related therapies. In the future, a better understanding of gut-liver-brain axis interactions will promote the development of novel preventative strategies and the discovery of precise therapeutic targets in multiple diseases.